Efeito da adição de ureia nas propriedades de adesivos fenólicos produzidos com óleo pirolitico de Eucalyptus sp. - Lúcio, Danielle de Moraes (2017)
The present work aimed to evaluate the effect of the addition of urea on properties of phenolic adhesives produced with oil from pyrolysis of Eucalyptus sp. Adhesives formulations were synthesized involving two formaldehyde/demethylated oil (F/DO) molar ratios (1.4 and 1.7), three sodium hydroxide/demethylated oil (NaOH/DO) molar ratios (0.9, 1.0 and 1.1) and five levels of urea (0, 5, 10, 15 and 20%). For all synthesized adhesives, the following properties and parameters were obtained: solids content (%), gel time (s), viscosity (cP), pH, reaction time (min) and temperature (°C). Plywood panels were produced with the purpose of evaluating the performance of the adhesive, for which the shear strength (Mpa) and the percentage of wood failure (%) in dry condition and after the boiling test were evaluated. Experimental data were subjected to quadratic regression analysis and models were adjusted for some adhesives properties and reaction conditions (time and temperature). Then tests were performed to verify the identity of regression models and equality of parameters. The experimental data of the plywood panels were submitted to analysis of variance. The simple correlation test indicates that there was influence in the percentages of urea in the adhesive properties. As urea levels increased, the gel time, reaction time, and temperature increased likewise. Better control of the synthesis could be obtained, avoiding the possibility of sudden gelatinization. As a conclusion, the synthesis reactions are more controllable under the following conditions: addition of urea in concentrations ranging from 5 to 10% with F/OD molar ratio of 1.7 and NaOH/OD molar ratio of 0.9. Adhesives produced with demethylated oil had lower shear strength and lower percentage of wood failure when compared to commercial phenolic adhesive in dry condition.